2014
DOI: 10.1002/mus.24435
|View full text |Cite
|
Sign up to set email alerts
|

Isolated leukemic infiltration of peripheral nervous system

Abstract: The presumed pathophysiology of isolated neuroleukemiosis is hematogenous spread of leukemic cells into the peripheral nervous system across the blood-nerve barrier. It should be considered in the differential diagnosis in patients with leukemia who present with neuropathy, even when they are considered to be clinically cured of leukemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 24 publications
2
22
0
4
Order By: Relevance
“…A blood–nerve barrier (BNB), similar to the blood–brain barrier (BBB), separates the circulating blood from the peripheral nerves [ 6 - 7 ]. The BNB is comprised of endoneurial vascular endothelial cells, a basement membrane and is surrounded by pericytes [ 6 ]. The tight intercellular junctions make it difficult for leukemic cells to penetrate.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A blood–nerve barrier (BNB), similar to the blood–brain barrier (BBB), separates the circulating blood from the peripheral nerves [ 6 - 7 ]. The BNB is comprised of endoneurial vascular endothelial cells, a basement membrane and is surrounded by pericytes [ 6 ]. The tight intercellular junctions make it difficult for leukemic cells to penetrate.…”
Section: Discussionmentioning
confidence: 99%
“…Wang, et al suggested that in patients with isolated neuroleukemiosis, a hematogenous spread of blast cells into the PNS is more likely than longitudinal dissemination from nerve root [ 6 ]. They proposed that pathogenic cells can penetrate an impaired BNB, and leukocytes can enter the PNS irrespective of any disturbance in the BNB [ 6 , 9 ]. Once the leukemic cells make it into the PNS they are in an ideal location to thrive, making them very difficult to treat.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations